2012
DOI: 10.1007/s11224-012-0058-3
|View full text |Cite
|
Sign up to set email alerts
|

First-row transition metal atoms adsorption on rutile TiO2(110) surface

Abstract: We performed periodic DFT calculations for adsorption of metal atoms on a perfect rutile TiO 2 (110) surface (at low coverage, h = 1/3) to investigate the interaction of an individual metal atom with TiO 2 and to compare it with a study previously done on MgO(100). We considered partial period of Mendeleev's table from K to Zn. The overall evolution of the adsorption energies shows two maxima as for MgO (100). Two main differences, however, exist: the adsorption energy is much stronger and the first maximum is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 68 publications
(97 reference statements)
4
12
1
Order By: Relevance
“…Furthermore, it was also observed that our computed adsorption energies are reasonably similar to the values described in the literature for the adsorption of SAC on the irreducible alumina (Al 2 O 3 ) surface, [22a, b, 51] but significantly weaker than those found for the reducible rutile (TiO 2 ) support [23] . As such, the adsorption of a single Pd, Pt or Cu atom on the α ‐Al 2 O 3 support is, respectively associated with an energy of −1.35, −2.20 and −0.70 eV, [22a, b, 51] whereas our calculations on the amorphous silica surface give rise to values of −1.21, −2.62 and −0.78 eV.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Furthermore, it was also observed that our computed adsorption energies are reasonably similar to the values described in the literature for the adsorption of SAC on the irreducible alumina (Al 2 O 3 ) surface, [22a, b, 51] but significantly weaker than those found for the reducible rutile (TiO 2 ) support [23] . As such, the adsorption of a single Pd, Pt or Cu atom on the α ‐Al 2 O 3 support is, respectively associated with an energy of −1.35, −2.20 and −0.70 eV, [22a, b, 51] whereas our calculations on the amorphous silica surface give rise to values of −1.21, −2.62 and −0.78 eV.…”
Section: Resultssupporting
confidence: 85%
“…From the current literature it can nonetheless be concluded that the strength by which these transition metal atoms adsorb on the surface is strongly driven by the above‐mentioned concept of SMSI. Accordingly, the adsorption of d‐transition metal atoms on defect‐free irreducible oxide supports (MgO, [20] SiO 2 [21] and Al 2 O 3 [22] ) will often be accompanied by less pronounced interactions than in the case of SMSI surfaces like TiO 2 [23] and CeO 2 [24] . While the metal‐support interactions in the non‐SMSI state often depend on a combination of effects such as van der Waals dispersion, polarization and sometimes orbital mixing, [20–21] the reducible character of TiO 2 and CeO 2 turns out to play a crucial role in the observed enhanced adsorption [22, 24] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption of the first TM row metals, as well as Pd, Ir, Pt and Au, has been studied using GGA-DFT on both pristine and defected rutile TiO 2 (110) surfaces. 58,59 Contrary to the results obtained for ZrO 2 and MgO, the adsorption energies of the studied metal atoms in the TiO 2 vacancy are typically more endothermic than or roughly equal to the corresponding energies on the ideal surface. 59 Only Au and, when the Hubbard correction was introduced, Pt bound more strongly inside a surface vacancy than on the ideal surface, though Pd and Ir were also noted as borderline cases.…”
Section: Adsorption and Reduction Energiescontrasting
confidence: 56%
“…Our calculations are periodic in three dimensions and we imposed a vacuum distance of 13 Å, which is large enough to avoid any interaction between two successive slabs. The model consists of nine atomic layers slab (three Ti 2 O 4 layers) of rutile oriented in the (110) direction, see Figure 5 [15,24,25]. We considered a double cell p(2x3) with a = 13.12 Å and b = 9.19 Å.…”
Section: Computational Detailsmentioning
confidence: 99%